Identification and characterization of pro-interleukin-16 from mud crab Scylla paramamosain: The first evidence of proinflammatory cytokine in crab species. Issue 70 (November 2017) - Gu, Wen-Bin; Zhou, Yi-Lian; Tu, Dan-Dan; Zhou, Zhong-Kai; Zhu, Qi-Hui; Chen, Yu-Yin; Shu, Miao-An
Abstract: IL-16 is a pro-inflammatory cytokine originally designated as a lymphocyte chemoattractant factor. In mammal and avian, it has been characterized as an essential regulator of various cellular processes including cell recruitment and activation against pathogen invasion. So far, neither of the full-length of IL-16 homologue nor the response mechanism against pathogen was reported in crab species. In the present study, the pro-IL-16 homologue was firstly cloned and characterized from mud crab Scylla paramamosain . The full-length Sp-pro-IL-16 consisted of 4107 bp with an opening reading frame encoding 1369 amino acids. Multiple alignment analysis showed the putative amino acid sequence of Sp-pro-IL-16 had about 73.86% identity with Litopenaeus vannamei pro-IL-16. Additionally, two conserved PDZ domains and protein binding sites were found in Sp- pro-IL-16 and showed high similarities about 94.19% and 51.14% with their Litopenaeus vannamei and Mus musculus counterparts. RT-PCR analysis indicated that Sp-pro-IL-16 transcripts were constitutively expressed in all tissues examined with an extreme high level in hepatopancreas. Moreover, Sp-pro-IL-16 transcripts in hepatopancreas were significantly up-regulated 15-fold at 72 h after Vibrio alginolyticus challenge and 3.5-fold at 12 h after virus-analog Poly (I:C) challenge. The Western blot analysis revealed that Sp- pro-IL-16 can be cleaved to its bioactive form, an approximately 35 kDa mature IL-16, and the protein levels of both pro-IL-16 and mature IL-16 increased after Vibrio alginolyticus challenge. It is the first experimental identification of pro-inflammatory cytokine IL-16 in arthropods. This study could shed new light on further understanding of the response mechanism of pro-inflammatory cytokine IL-16 in Scylla paramamosain against pathogens. Meanwhile, it brought new insight into the origin and evolution of IL-16 in crab species. Highlights: First identified and characterized proinflammatory cytokine IL-16 in crab species. Confirmation of early divergence during evolutionary process by phylogenetic analysis. Expression pattern analyzed and found to be correlated with the pathogen infection. Cleavage confirmed from pro-IL-16 to mature IL-16 in protein level. Provide new insight into the origin and evolution of proinflammatory cytokine IL-16 in crabs and even in invertebrates.